Maintaining altruism among nursing professionals - Kaul, Priyanka; Singh, Ankit (International Journal of Public Health Science (IJPHS), 2024)
The demanding hospital work environment has increased the need for organizational citizenship behaviour (OCB). It’s essential to maintain the altruistic behaviour of nursing professionals towards each other to enhance the patient experience and provide quality healthcare service to patients efficiently. This quantitative study explored the relationships between OCB constructs based on social identity theory (SIT) and system justification theory (SJT). This study is empirical and cross-sectional in nature; structural equation modeling is performed on two hundred twenty-two nursing professional responses, using IBM AMOS V.22 to test the hypothesized model. Conscientiousness has a mediating effect on the relationship between civic virtue and altruism (Indirect effect=0.19, Boot SE=.057, lower-level confidence interval (LLCI)=.0940, upper-level confidence interval (ULCI)=.3144). Moreover, sportsmanship had a mediating effect on the relationship between civic virtue and altruism with an Indirect effect=-0.06, Boot SE=.023, LLCI=-0.1159, ULCI=-0.0222). The results supported the hypothesis that civic virtue and altruism are directly related and found that conscientiousness and sportsmanship mediate the relationship between civic virtue and altruism. The findings suggest that employees with higher sportsmanship tend to reduce their altruistic behavior in the long run.